2004
DOI: 10.1186/ar1207
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen receptor-α gene haplotype is associated with primary knee osteoarthritis in Korean population

Abstract: Estrogen and estrogen receptors (ERs) are known to play important roles in the pathophysiology of osteoarthritis (OA). To investigate ER-α gene polymorphisms for its associations with primary knee OA, we conducted a case-control association study in patients with primary knee OA (n = 151) and healthy individuals (n = 397) in the Korean population. Haplotyping analysis was used to determine the relationship between three polymorphisms in the ER-α gene (intron 1 T/C, intron 1 A/G and exon 8 G/A) and primary knee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
16
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(21 citation statements)
references
References 24 publications
(22 reference statements)
3
16
0
Order By: Relevance
“…Noteworthy, the C allele frequency of rs2234693 and the G allele frequency of rs9340799 in controls were 0.379 and 0.185, respectively, which were similar to those observed in the Japanese and Korean populations [13, 15] whereas different from those in European and American Caucasians to a certain degree [17, 18]. We also proposed the predisposing roles of T allele of rs2234693 in the etiology of knee OA, and this was partially in concordance with the protective effects of C allele in Japanese and Caucasians [17, 18] but against the observation that CC genotype was a risk factor of radiographic knee OA in a Rotterdam study [14].…”
Section: Discussionsupporting
confidence: 79%
“…Noteworthy, the C allele frequency of rs2234693 and the G allele frequency of rs9340799 in controls were 0.379 and 0.185, respectively, which were similar to those observed in the Japanese and Korean populations [13, 15] whereas different from those in European and American Caucasians to a certain degree [17, 18]. We also proposed the predisposing roles of T allele of rs2234693 in the etiology of knee OA, and this was partially in concordance with the protective effects of C allele in Japanese and Caucasians [17, 18] but against the observation that CC genotype was a risk factor of radiographic knee OA in a Rotterdam study [14].…”
Section: Discussionsupporting
confidence: 79%
“…Our data has shown significant alterations in the distribution of variant alleles of GDF-5, ESR- α , and CALM-1 in OA cases when compared to the controls. Similar to the case control studies involving Caucasians and Oriental people [ 9 , 11 , 16 18 , 27 ], an increase in the frequency of A allele (rs 2228480) was observed in OA patients when compared with the controls. Significant increase in the frequency of risk allele (T) of GDF-5 in cases of osteoarthritis is consistent with previous report demonstrating association of polymorphism in GDF-5 with OA [ 9 , 11 ].…”
Section: Discussionsupporting
confidence: 72%
“…Polymorphism in ESR- α gene was detected by the method of Jin et al 2004 [ 16 ]. In brief the PCR product formed was digested with BtgI for identifying (rs2228480) polymorphism.…”
Section: Dna Isolation and Genotyping Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Inheritance studies involving family groups and twin pairs have demonstrated that a large proportion of OA cases can be attributed to genetic factors, suggesting that the etiology of OA clearly has a genetic component [9,10]. In recent years, a number of gene polymorphisms involved in development of knee OA have been identified, such as those localized in, or adjacent to the encoding sequences for the vitamin D receptor [11], estrogen receptor alpha [12] or calcitonin [13]. …”
Section: Introductionmentioning
confidence: 99%